Evaluation of an outbred mouse model for Francisella tularensis vaccine development and testing. - Raju Sunagar; Sudeep Kumar; Prachi Namjoshi; Sarah J Rosa; Karsten R O Hazlett; Edmund J Gosselin (PLoS ONE, 2018)
Francisella tularensis (Ft) is a biothreat agent for which there is no FDA-approved human vaccine. Currently, there are substantial efforts underway to develop both vaccines and the tools to assess these vaccines. Tularemia laboratory research has historically relied primarily upon a small number of inbred mouse strains, but the utility of such findings to outbred animals may be limited. Specifically, C57BL/6 mice are more susceptible than BALB/c mice to Ft infection and less easily protected against challenge with highly virulent type A Ft. Thus, depending on the inbred mouse strain used, one could be misled as to which immunogen(s)/vaccine will ultimately be effective in an outbred human population. Accordingly, we evaluated an outbred Swiss Webster (SW) mouse model in direct comparison to a well-established, inbred C57BL/6 mouse model. Mucosal vaccination with the live, attenuated Ft LVS superoxide dismutase (sodB) mutant demonstrated significantly higher protection in outbred SW mice compared to inbred C57BL/6 mice against Ft SchuS4 respiratory challenge. The protection observed in vaccinated outbred mice correlated with lower bacterial density, reduced tissue inflammation, and reduced levels of pro-inflammatory cytokine production. This protection was CD4+ and CD8+ T cell-dependent and characterized by lower titers of serum antibody (Ab) that qualitatively differed from vaccinated inbred mice. Enhanced protection of vaccinated outbred mice correlated with early and robust production of IFN-γ and IL-17A. Neutralizing Ab administered at the time of challenge revealed that IFN-γ was central to this protection, while IL-17A neutralization did not alter bacterial burden or survival. The present study demonstrates the utility of the outbred mouse as an alternative vaccination model for testing tularemia vaccines. Given the limited MHC repertoire in inbred mice, this outbred model is more analogous to the human in terms of immunological diversity.